Risks Involved in the Use of Enrofloxacin for Salmonella Enteritidis or Salmonella Heidelberg in Commercial Poultry - Morales-Barrera, Eduardo; Calhoun, Nicole; Lobato-Tapia, Jose L.; Lucca, Vivian; Prado-Rebolledo, Omar; Hernandez-Velasco, Xochitl; Merino-Guzman, Ruben; Petrone-García, Victor M.; Latorre, Juan D.; Mahaffey, Brittany D.; Teague, Kyle D.; Graham, Lucas E.; et al. (Frontiers in Veterinary Science, 2016)
The objectives of the present study were to evaluate the risks involved in the use of Enrofloxacin for Salmonella Enteritidis (SE) or Salmonella Heidelberg (SH) in commercial poultry and determine the effects of a probiotic as an antibiotic alternative. Two experiments were conducted to evaluate the risks involved in the use of Enrofloxacin for SE or SH in commercial poultry. Experiment 1 consisted of two trials. In each trial, chickens were assigned to one of three groups; control + SE challenged; Enrofloxacin 25 mg/kg + SE; and Enrofloxacin 50 mg/kg + SE. Chickens received Enrofloxacin in the drinking water from days 1 to 5 of age. On day 6, all groups received fresh water without any treatment. All chickens were orally gavaged with 107 cfu/chick of SE at 7 days of age and euthanized on 8 days of age. In Experiment 2, turkey poults were assigned to one of the three groups; control + SH; probiotic + SH; and Enrofloxacin 50 mg/kg + SH. Poults received probiotic or Enrofloxacin in the drinking water from days 1 to 5 of age. On day 6, poults received fresh water without any treatment. Poults were orally gavaged with 107 cfu/poult of SH at 7 days of age. Poults were weighed and humanely killed 24 h post-SH challenge to evaluate serum concentration of fluorescein isothiocyanate-dextran to evaluate intestinal permeability, metagenomics, and SH infection. In both trials of Experiment 1, chickens treated with Enrofloxacin were more susceptible to SE organ invasion and intestinal colonization when compared with control non-treated chickens (P < 0.05). In Experiment 2, poults treated with 50 mg/kg of Enrofloxacin showed an increase in body weight, however, this group also showed an increase in SH susceptibility, intestinal permeability, and lower proportion of Firmicutes and Bacteroidetes, but with control group had the highest proportion of Proteobacteria. By contrast, poults that received the probiotic had the highest proportion of Firmicutes and Bacteroidetes, but lowest Proteobacteria. The results of the present study suggest that prophylactic utilization of Enrofloxacin at five times the recommended dose in poultry increases the susceptibility to salmonellae infections, and confirms that probiotics may be an effective tool in salmonellae infections.